CS-08 Effect of antimalarials over the different domains of the damage index in latin american SLE patients. (August 2018) - Pons-Estel, Bernardo; Wojdyla, Daniel; Alarcón, Graciela S; Serrano, Rosa María; Quintana, Rosana; Ugarte-Gil, Manuel; Pimentel-Quiroz, Víctor; Soriano, Enrique R; Scolnik, Marina; Sacnun, Mónica; Gómez-Puerta, José A; Cardiel, Mario H; et al.
Abstract : Background: We have previously shown that Latin American SLE patients treated with Antimalarials (AMs) have a 25% lower risk of damage accrual than patients not receiving them. The present study was conducted to assess the effects of AMs over the 12 items of the SLICC Damage Index, (SDI). Methods: Patients with a recent SLE diagnosis (≤2 years) from the GLADEL cohort were studied. End-point: Increase in the 12 items SDI since cohort entry. Independent (socio-demographic, clinical laboratory and treatment) variables were included. The effect of AMs as a time dependent variable on items of the SDI (adjusting for potential confounders) was examined with a multivariable Cox regression model. Multivariate models were developed for the most common SDI items. Results: Of the 1466 patients included in this analysis 1049 (72%) received AMs during follow-up (as defined); median exposure time: 30 months (Q1-Q3: 11–57 months). Total damage accrual occurred in 665 (45%) patients during a median follow up time of 24 months (Q1-Q3: 8–55) months. Within the 12 items of the SDI there were 301 integument, 208 renal, 149 neuropsychiatric, 98 musculoskeletal, 88 cardiovascular, 65 ocular, 43 pulmonary, 42 peripheral vascular, 33 gastrointestinal, 22 premature gonadal failure, 16 diabetes and 9 malignancy. After adjusting for potential confounders, at any time during follow-up a patient on AMs had a 35% and 30% lower risk of renal and neuropsychiatric damage accrual respectively than a patient not on AMs (adjusted HR 0.65, 95% CI 0.47 to 0.90 and HR 0.70, 95% CI 0.48 to 1.02). Such protective effect was not evident for integument, musculoskeletal and cardiovascular damage. Table 1. Conclusions: After adjustment for possible confounding factors related to AMs use and damage accrual, AMs were independently associated with a reduced risk of renal and neuropsychiatric damage accrual in this cohort. Acknowledgements: On behalf of the Grupo Latinoamericano de Estudio del Lupus (GLADEL).